Expressive Renewal, Gender and Identities in Carmen Troitiño’s two Early Plays: Pandereta (1949) and Pasiones (1952) (Castilla. Estudios de Literatura, 2026)
in this essay, we study the first two plays published in post-war Spain by Carmen Troitiño —author, stage director, and theatre promoter— from a gender perspective: Pandereta (1949) and Pasiones (1952). The analysis of both texts focuses on the construction of male and female identities, in order to determine to what extent they adhere to the model of femininity/masculinity promoted by the regime, and the possible transgressions that occur. Likewise, the essay examines the generic and expressive channels chosen by the author in both plays, which, in general terms, are far from the model of the escapist comedy that was successful on stages during these years.
Keywords: female playwrights; Carmen Troitiño; Francoism; Gender identities; expressive renewal